(untitled) ("Journal "U". Economy. Management. Finance.", 2022)
Trade is an important branch of the Russian economy, accounting for about 13% of GDP. The turnover per trade organization characterizes the volume of sales of wholesale and retail trade, and the higher this indicator, the better the financial condition of these organizations. This article presents an analysis of the dynamics of the volume of trade turnover per trade organization to Russia, identifies a trend and makes point and interval forecasting of the studied indicator.